2018
DOI: 10.1111/cbdd.13408
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and antiplasmodial evaluation of a series of novel sulfoximine analogues of carbohydrate‐based thiochromans

Abstract: Sulfone/sulfoxide-containing carbohydrate derived thiochromans were found to be highly active antiplasmodial agents. However, the inability of the sulfone/sulfoxide functional groups for further derivatization and manipulation limited the potential for further exploration. In this study, based on the interesting and important physicochemical properties, as well as amenability of sulfoximines (isosters of sulfones) for further derivatization, a series of novel sulfoximine-type carbohydrate-derived thiochroman d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Additionally, all investigated compounds were not cytotoxic against HeLa cells at 20 μM. 149 The phenyl residue or the triazole moiety was not examined; hence, the authors concluded that 71 may serve as a prototype for novel derivatives with improved antiplasmodial activities. Further investigations of the SAR, ADME profile, and in vivo potency of this class of compounds are needed to reach clinical trials.…”
Section: Sulfoximines As a Novel Lead Structure Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, all investigated compounds were not cytotoxic against HeLa cells at 20 μM. 149 The phenyl residue or the triazole moiety was not examined; hence, the authors concluded that 71 may serve as a prototype for novel derivatives with improved antiplasmodial activities. Further investigations of the SAR, ADME profile, and in vivo potency of this class of compounds are needed to reach clinical trials.…”
Section: Sulfoximines As a Novel Lead Structure Inmentioning
confidence: 99%
“…(A) Chemical structures and IC 50 values of the parent carbohydrate-based thiochroman 69 and its sulfoximine analogues 70a / b . (B) chemical structure and IC 50 value of the most potent sulfoximine-triazole hybrid 71 . ,,, …”
Section: Sulfoximines As a Novel Lead Structure In Medicinal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As part of their broader studies in carbohydrate chemistry, Kinfe et al. described the synthesis and biological activity of a series of carbohydrate derived thiochromans, which possessed sub‐micromolar activity against chloroquine‐sensitive and ‐resistant strains in vitro In order to further explore this class of compounds, Chizema et al., explored bioisosteric replacement of the sulfone functionality with a sulfoximine (e. g., 71 ), which in addition to favourable physicochemical properties, and metabolic stability, has the distinct advantage of introduction of a stereogenic centre, which can be further functionalised . Following biological assessment, these compounds were generally found to be moderate anti‐plasmodials, with activities in the low‐micromolar range, and represent an interesting scaffold for further elaboration …”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…The increasing interest in sulfoximines in drug discovery, medicine, and agrochemistry , has led to a rapidly growing number of publications in these and other research areas . These compounds are of great importance as ligands, auxiliaries, and catalysts, e.g., in asymmetric synthesis and catalysis. , Recently, a large number of reports on their synthesis and transformations have appeared in the literature, including halo- and chalcogenations.…”
mentioning
confidence: 99%